Exploring the interpretation techniques in Bach’s Cello Suite No. 1 Prelude: A theoretical and practical approach to baroque performance practice - Nandya Abror Nurmusabih; Andhika Dzaki Naufal (Universitas Pendidikan Indonesia, 2024)
This study investigates the essential strategies for interpreting Johann Sebastian Bach's Cello Suite No. 1 Prelude, with a specific emphasis on historically informed performance practices (HIP). The focus of this study is the intricate implementation of Baroque performance methods, including slurs, detached notes, double stops, cross-string techniques, and ornamentation. These skills are crucial for providing a faithful interpretation of Bach's music. The significance of this research is to connect historical performance techniques with present interpretative approaches, guaranteeing that contemporary performers may give performances that are both historically precise and emotionally captivating. The research methodology employed in this study involves an extensive examination of relevant literature, specifically focusing on the contributions of prominent academics such as Frederick Neumann, David Schulenberg, and Jean Claude Veilhan. These scholars have offered valuable insights into the fundamental aspects of Baroque performance practices. Furthermore, this analysis examines the incorporation of historical knowledge with contemporary performance practices by studying the practical insights of esteemed cellists such as Anner Bylsma and Pieter Wispelwey. This dual approach enables a comprehensive comprehension of both the theoretical foundations and actual implementations of the performance strategies in question. This research emphasizes the crucial function of slurs in producing smooth and connected phrasing, the significance of detached notes for precise rhythm, the utilization of double stops and cross-string techniques to enhance harmonic richness and technical complexity, and the importance of ornamentation in deepening the expressive quality of the Prelude. This research offers a complete framework for interpreting Bach's Cello Suite No. 1 Prelude by combining theoretical analysis with practical performance suggestions. This technique not only respects the artistic authenticity of Baroque music but also guarantees that Bach's enduring masterpiece remains relevant to contemporary audiences, thus contributing to the continuous development of classical music performance.